A comprehensive global modeling assessment of nitrate heterogeneous formation on desert dust - R. Soussé Villa; O. Jorba; M. Gonçalves Ageitos; M. Gonçalves Ageitos; D. Bowdalo; M. Guevara; C. Pérez García-Pando; C. Pérez García-Pando (Atmospheric Chemistry and Physics)
Desert dust undergoes complex heterogeneous chemical reactions during atmospheric transport, forming nitrate coatings that influence hygroscopicity, gas partitioning, optical properties, and aerosol radiative forcing. Contemporary atmospheric chemistry models show significant disparities in aerosol nitrogen species due to varying parameterizations and inaccuracies in representing heterogeneous chemistry and dust alkalinity. This study investigates key processes in nitrate formation in the presence of dust and evaluates their representation in models. We incorporate varying levels of dust heterogeneous chemistry complexity into the Multiscale Online Nonhydrostatic AtmospheRe CHemistry (MONARCH) model, assessing sensitivity to critical processes. Our analyses address the condensation pathways of gas species onto dust (irreversible and reversible); the influence of nitrate representation on species burdens, lifetimes, and size distribution; and the role of alkalinity. Using annual global simulations, we compare particulate and gas species surface concentrations to observations and evaluate global budgets and spatial distributions. Findings show significant outcome dependence on methodology, particularly on reversible vs. irreversible gas condensation on dust, with wide ranges for particulate nitrate burdens (0.66 to 1.93 Tg) and correlations with observations (0.66 to 0.91). In contrast, particulate ammonium burdens show lower variability (0.19 to 0.31 Tg). Incorporating dust (together with sea-salt) alkalinity improves consistency with observations, with reversible condensation along with alkalinity representation yielding the best agreement, while showing consistent gas and particle partitioning. In contrast, irreversible uptake reactions overestimate coarse particulate nitrate formation. Our findings offer guidelines for integrating nitrate heterogeneous formation on dust in models, paving the road for improved estimates of aerosol radiative effects.